(untitled) (Revista Sistemas de Producción Agroecológicos, 2016)
In this document highlights the importance of the tree species used in the feeding of animals of zootechnical interest, and how the different conservation alternatives allow to supply a food of excellent nutritional quality in times of scarcity. As it is known, the efficient feeding Is one of the most important aspects in animal production, because of this depends not only on the zootechnical performance of the animals, if not also the economic profitability of the producer. To provide a good diet, the food must be supplied with the necessary amount of nutrients in optimal physical conditions so that the same be metabolically used of form efficient and thus to obtain the maximum yield in the production. The food supply in non-conventional form allows to explore new alternatives which provide good quality food in the search for low-cost food sources in the tropics, the evaluation of tree foliage has been included due to its high availability; the use of flours of plant foliage has been considered as an option for the partial or total substitution of protein mainly from grains and cereals for animal feed being currently one of the strategies of greater research, where facilitating their inclusion in the balanced diets of animals becomes an economic alternative which will replace in part the use of commercial concentrated food. Tree species such as Gliricidia sepium, Leucaena leucocephala, Guazuma ulmifolia, Hibiscus rosa-sinensis and Morus alba are of interest to the producer because of their production potential (21.93-30.6 ton/ha/DM).